Not all robots - Russell, Mark 1971- (Artists, Writers & Artisans, Inc., 2023)
In the year 2056, robots have replaced human beings in the workforce. An uneasy co-existence develops between the newly intelligent robots and the ten billion humans living on Earth. Every human family is assigned a robot upon whom they are completely reliant. What could possibly go wrong? Meet the Walters, a human family whose robot, Razorball, ominously spends his free time in the garage working on machines which they're pretty sure are designed to kill them
Keywords: Robots -- Comic books, strips, etc; Labor supply -- Comic books, strips, etc; Artificial intelligence -- Comic books, strips, etc; Families -- Comic books, strips, etc; Arbeitsangebot; Künstliche Intelligenz; Roboter; Comic